KERANGKA PEMIKIRAN TENTANG STRATEGI INTERVENSI MASYARAKAT - Istiana Hermawati (Politeknik Kesejahteraan Sosial, 2003)
An Idea of Social Intervention Strategy In the frame tc increase people participation in social development, many activies in community intervention has implemented. The essention of the activity is a community empowerment process to gain self reliance, which people can solve their problems, and met their need. The empowerment process through community intervention has several models. These are community development / locality development model, social planning and policy mode l, and social action model. In social development context through the strategy of community intervention, community worker can do their functions as an enabler, broker, social planner, educator, expert, advocate, and activist. Have as a starting point on situation, condition, problems and needs that felt by Indonesia people, so the strategy of community intervention that relevant to implement is locality development model with bottom up approach. Nevertheles, in order to effort social development can effective in realization throughh implementation this model, should supported by both of another models, those are social planning and policy, and social action models, so social welfare that we expected, relatively will be come true